1982
DOI: 10.1161/01.cir.66.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the extent of the zone at risk on the effectiveness of drugs in reducing infarct size.

Abstract: SUMMARY The goal of this study was to examine whether the effectiveness of a drug in protecting ischemic myocardium depends on the size of the hypoperfused zone (the area at risk) measured immediately after coronary artery occlusion (CAO). Methoxy-verapamil (D600), a potent calcium antagonist, was used to test this hypothesis. In 68 dogs, 1 minute after CAO, 8 mCi of technetium-99m-labeled albumin microspheres were injected into the left atrium for later assessment of the hypoperfused zone by autoradiography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Close correlation between area of risk, as demonstrated by MB staining, and area of infarction, as shown by TTC staining, has previously been demonstrated after 6 hr of occlusion without a myocardial salvaging intervention. 17 18 Thus, the extent of infarction also correlated well with that of ECD in our series in which no attempt was made at salvage. The extent of the ECD was a considerably more accurate indicator of the state of The correlation is higher and the estimating error is smaller for percent circumferential extent of abnormality at all levels for ECD vs MB than for ECD vs TTC, indicating that ECD corresponds to malperfusion rather than infarction.…”
Section: Discussionsupporting
confidence: 63%
“…Close correlation between area of risk, as demonstrated by MB staining, and area of infarction, as shown by TTC staining, has previously been demonstrated after 6 hr of occlusion without a myocardial salvaging intervention. 17 18 Thus, the extent of infarction also correlated well with that of ECD in our series in which no attempt was made at salvage. The extent of the ECD was a considerably more accurate indicator of the state of The correlation is higher and the estimating error is smaller for percent circumferential extent of abnormality at all levels for ECD vs MB than for ECD vs TTC, indicating that ECD corresponds to malperfusion rather than infarction.…”
Section: Discussionsupporting
confidence: 63%
“…Data from three dogs (all in the pretreatment group) with hypoperfused zones smaller than 10% of the left ventricle were excluded from the analyses of the effects of nicardipine on the incidence of ventricular arrhythmias and on myocardial infarct size after coronary artery occlusion, because it has been demonstrated that both the occurrence of ventricular arrhythmias and the effectiveness of an intervention to reduce infarct size depend on the extent of the hypoperfused zone, and that the smaller the hypoperfused zone, the less frequent the ventricular arrhythmia and the more effective the treatment.34 41 Ventricular arrhythmias and mortality. Ventricular fibrillation did not occur during reperfusion after temporary (5 min) coronary artery occlusion.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study in anaesthetised dogs this principle has been applied, but a number of problems were encountered, this experience led us to redefine the most appropriate method for our purpose, as existing experimental procedures in dogs are not very reproducible or economical. Large numbers of animals have been required (31,43), and the results with drug treatments controversial (28,34,48,55). Previous work has emphasised the important difference between permanent coronary artery occlusion and temporary occlusion followed by reperfusion (41).…”
Section: Introductionmentioning
confidence: 99%